GREEN CONCRETE INNOVATION: UTILIZING AGRICULTURAL WASTE ASH IN HIGH-STRENGTH CONTRUCTION MIXES - Shazia Akhtar; Thiago Rocha; Zhou Hui (Yayasan Adra Karima Hubbi, 2025)
The construction industry is one of the largest contributors to global carbon emissions, primarily due to cement production. As a result, there is an increasing demand for sustainable alternatives that reduce environmental impact while maintaining high-performance standards. This study explores the use of agricultural waste ash, such as rice husk ash, palm oil shell ash, and sugarcane bagasse ash, as a partial replacement for cement in high-strength concrete mixes. The main objective of this research is to investigate the effects of agricultural waste ash on the mechanical properties and environmental sustainability of high-strength concrete. A comprehensive experimental approach was adopted, involving the preparation of concrete mixes with varying percentages of agricultural waste ash (5%, 10%, 15%, and 20%) and standard tests to assess compressive strength, durability, and environmental impact. The results show that incorporating agricultural waste ash improves the compressive strength and durability of high-strength concrete while significantly reducing the carbon footprint. The study concludes that agricultural waste ash is a viable and sustainable alternative to traditional cement, offering both economic and environmental benefits for the construction industry. The research contributes to the growing body of knowledge on green concrete innovations and provides valuable insights for sustainable construction practices.